Answer:
900,000
Step-by-step explanation:
there you go bud
7(x - 3) + 3(4 - x) = -8
7x - 21 + 12 - 3x = -8
7x - 3x = -8 + 21 - 12
4x = 1
x = 1/4
Answer:
d < 8
Step-by-step explanation:
Given
- 12 + 8d < 52 ( add 12 to both sides )
8d < 64 ( divide both sides by 8 )
d < 8
cos4x = cos2x
We know that:
cos2x = 1-2cos^2 x
==> cos4x = 1-2cos^2 (2x)
Now substitute:
==> 1-2cos^2 (2x) = cos2x
==> 2cos^2 (2x) + cos2x - 1 = 0
Now factor:
==> (2cos2x -1)(cos2x + 1) = 0
==> 2cos2x -1 = 0 ==> cos2x =1/2 ==> 2x= pi/3
==> x1= pi/6 , 7pi/6
==> x1= pi/6 + 2npi
==> x2= 7pi/6 + 2npi
==> cos2x = -1 ==> 2x= pi ==> x3 = pi/2 + 2npi.
<span>==> x= { pi/6+2npi, 7pi/6+2npi, pi/2+2npi}</span>